2014
DOI: 10.1002/jqs.2730
|View full text |Cite
|
Sign up to set email alerts
|

Orbital‐ and millennial‐scale climate and vegetation changes between 32.5 and 6.9k cal a BP from Hanon Maar paleolake on Jeju Island, South Korea

Abstract: Orbital‐ and millennial‐scale climate and vegetation changes between 32.5 and 6.9k cal a BP from Hanon Maar paleolake on Jeju Island, Korea, were demonstrated by high‐resolution multi‐proxy data (pollen, magnetic susceptibility, total organic carbon, carbon/nitrogen ratios and sediment grain size). High‐resolution pollen records provided detailed information on the vegetation response to climate change. The Thalictrum pollen percentage, which corresponded to the magnetic susceptibility data, and the first prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Abbott et al, 2010); Finkenbinder et al, 2015;Fischer et al, 2015), Asia (e.g. Park et al, 2014) and Europe (e.g Guiter et al, 2003;Feurdean et al, 2014;Birks and Birks, 2014;Pickarski et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Abbott et al, 2010); Finkenbinder et al, 2015;Fischer et al, 2015), Asia (e.g. Park et al, 2014) and Europe (e.g Guiter et al, 2003;Feurdean et al, 2014;Birks and Birks, 2014;Pickarski et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Severe dry and cold climate in this period might have led to an interruption of sedimentation in the swamp, which probably resulted from the low summer insolation coupled with low sea level and declined land‐sea thermal contrast over East Asia. Severe dry climate during the LGM has been reported by various natural archives in EASM region (An et al, ; Lu et al, ; Park et al, ; Wang et al, ). Zhao et al () also found that there were very few basal dates of peat initiation corresponding to LGM across monsoonal China due to the very low summer insolation.…”
Section: Discussionmentioning
confidence: 98%
“…The frequency of Botryococcus is sometimes a very good climate-sensitive indicator of aquatic productivity 25 . It has been particularly useful in paleoenvironmental studies of sediment cores from Jeju Island 20 , 21 , 75 , 76 . A pollen diagram was produced using TILIA 77 .…”
Section: Methodsmentioning
confidence: 99%